GAMBAR CADAS SITUS KOMPLEKS CERUK WABURI, BUTON SELATAN - Sarsina Meyni Usman; syahrun Syahrun; salniwati salniwati (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2020)
ABSTRACT The Waburi niche complex site is the first prehistoric site found in South Buton District which has archaeological remains in the form of rock art in four niches surveyed on Konawe Beach. This study discusses variations in the form and technique of rock drawing at the Waburi niche complex site. The research method used is a picture description and rock shooting which will be processed using D'Stretch software for sharpening colors and shapes. In addition, the classification of forms is based on their attributes and analysis uses morphological and technological analysis to determine the diversity of image shapes and drawing techniques at the Waburi niche complex site. It is known that rock art at the Waburi Ceruk Complex Site have 87 rock images with pictographic motifs namely boat and hand drawings, ideographic motifs that are diverse geometric drawings and psychographic motifs which are abstract drawings. While the drawing technique uses pictograph techniques. Keywords: Rock Art ; Image Variation; Niche